Dynamic heat transfer characteristics of ice storage in smooth-tube and corrugated-tube heat exchangers. (25th March 2023) - Li, Chengjun; Hou, Juan; Wang, Yaran; Wei, Shen; Zhou, Pengkun; He, Zhihao; Wang, Yeming; Zhang, Huan; You, Shijun
Highlight: One-dimensional numerical model of the corrugated-tube and smooth-tube heat exchangers. Performance comparison of the two heat exchangers via the validated numerical model. The ice-storage and melting duration of corrugated-tube heat exchanger is shorter. The heat exchange rate of corrugated exchanger is 2.5 and 9 times to smooth exchanger. Abstract: The ice storage system is one of the most promising techniques for flexibility enhancement of building cooling load. In this paper, the performances of smooth-tube and corrugated-tube heat exchangers for ice storage are compared by experiments and numerical simulation. The heat transfer process of the ice storage and melting within the heat exchangers is numerically analyzed used Python. The fast one-dimensional numerical model is verified by the experimental results. The temperature variation of the heat transfer fluid (HTF) in the corrugated tube is analyzed and compared with that in the smooth tube. The results show that under the same conditions, the ice storage duration of the corrugated tube is shortened by 25% and the melting duration is shortened by 16% compared with those of the smooth tube. During the ice storage process, the temperature difference between the inlet and outlet of the heat transfer fluid in the corrugated tube is 0.4 °C less than that of the smooth tube on average. The temperature change rate is 30% faster than that of the smooth tube. During the melting process, the temperature difference between the inlet and outlet of the heat transfer fluid in the corrugated tube is 0.1 °C higher than that of the smooth tube on average, and the temperature change rate of corrugated-tube heat exchanger is 2.5 times and 9 times faster than that of the smooth tube during the ice-storage and melting process. The corrugated-tube heat exchanger has superior performances in ice storage system in the comparison with the smooth-tube heat exchanger.